The Potential of Recycled Aggregates and Coconut Fiber in the Production of Concrete - Alabi, Stephen Adeyemi (International Journal of Integrated Engineering, 2020)
The high cost of conventional construction materials has led researchers into the search for alternative construction materials that are sustainable and eco-friendly. This study investigates the effect of crushed sandscrete block as recycled fine aggregate (RFA) and crushed abandoned cubes as recycled coarse aggregate (RCA) with constant percentage of coconut fibre (CF) on the properties of the concrete. The normal aggregate concrete (NAC) containing normal aggregate (NA) without the addition of CF was first produced and tested. The second stage involved production of concrete comprising constant percentage of CF with 25%, 50%, 75% and 100% fine and coarse aggregate replacement by weight with RFA and RCA. Properties of fresh and hardened concrete for all specimen types with standard procedure to obtain an optimum mix design was determined. The results obtained from the study shows that the workability of all the replacements were found to be lower than that of the normal aggregate concrete (NAC). Compressive and splitting tensile strength test showed that at optimum replacement levels of 25% RCA and 25% RFA concrete have better strength performance than NAC. The study established that RCA and RFA is capable of partially replacing NA in concrete production in ternary form. The optimum percentage replacement of RCA, RFA and CF should be adhered to for effective performance.